Acylated ghrelin treatment normalizes skeletal muscle mitochondrial oxidative capacity and AKT phosphorylation in rat chronic heart failure. Issue 6 (3rd November 2017) - Barazzoni, Rocco; Gortan Cappellari, Gianluca; Palus, Sandra; Vinci, Pierandrea; Ruozi, Giulia; Zanetti, Michela; Semolic, Annamaria; Ebner, Nicole; von Haehling, Stephan; Sinagra, Gianfranco; Giacca, Mauro; Springer, Jochen
Abstract: Background: Chronic heart failure (CHF) is associated with skeletal muscle abnormalities contributing to exercise intolerance, muscle loss, and negative impact on patient prognosis. A primary role has been proposed for mitochondrial dysfunction, which may be induced by systemic and tissue inflammation and further contribute to low insulin signalling. The acylated form of the gastric hormone ghrelin (AG) may improve mitochondrial oxidative capacity and insulin signalling in both healthy and diseased rodent models. Methods: We investigated the impact of AG continuous subcutaneous administration (AG) by osmotic minipump (50 nmol/kg/day for 28 days) compared with placebo (P) on skeletal muscle mitochondrial enzyme activities, mitochondrial biogenesis regulators transcriptional expression and insulin signalling in a rodent post‐myocardial infarction CHF model. Results: No statistically significant differences (NS) were observed among the three group in cumulative food intake. Compared with sham‐operated, P had low mitochondrial enzyme activities, mitochondrial biogenesis regulators transcripts, and insulin signalling activation at AKT level ( P < 0.05), associated with activating nuclear translocation of pro‐inflammatory transcription factor nuclear factor‐κB. AG completely normalized all alterations ( P < 0.05 vs P, P = NS vs sham‐operated). Direct AG activities were strongly supported by in vitro C2C12 myotubes experiments showing AG‐dependent stimulation of mitochondrial enzyme activities. No changes in mitochondrial parameters and insulin signalling were observed in the liver in any group. Conclusions: Sustained peripheral AG treatment with preserved food intake normalizes a CHF‐induced tissue‐specific cluster of skeletal muscle mitochondrial dysfunction, pro‐inflammatory changes, and reduced insulin signalling. AG is therefore a potential treatment for CHF‐associated muscle catabolic alterations, with potential positive impact on patient outcome.